(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the importance of equipping future primary school teachers with the necessary skills and competencies to effectively utilize non-traditional teaching methods in modern educational settings. As education systems evolve and diversify, traditional approaches to teaching are increasingly being supplemented—or even replaced—by more creative, student-centered, and interactive methods. The paper discusses how integrating non-traditional pedagogical strategies such as project-based learning, role-play, gamification, inquiry-based instruction, and the use of digital tools can enhance student engagement, critical thinking, and knowledge retention in primary education. Special attention is given to the pedagogical training of future teachers, highlighting the need for systematic curriculum reforms in teacher education institutions. The study analyzes current teacher training models, identifies gaps in practical application, and proposes specific strategies for improving methodological preparation. These include increased emphasis on hands-on workshops, collaboration with experienced educators, and opportunities for micro-teaching with feedback. Through a combination of theoretical research and field observations, the article demonstrates that preparing primary school teachers to adopt innovative methodologies is not only beneficial for classroom outcomes but also crucial for the development of adaptable and competent professionals. The findings suggest that the integration of non-traditional methods requires a shift in educational philosophy—moving from teacher-centered to learner-centered paradigms. Ultimately, the article advocates for a multidimensional approach to teacher development that blends theory, practice, and reflective learning to prepare future educators for the dynamic challenges of 21st-century classrooms.